Providing Visions of a Different Life:: Self-study Narrative Inquiry as an Instrument for Seeing Ourselves in Previously-Unimagined Places - Shields, Carmen; Novak, Nancy; Marshall, Brenda; Guiney Yallop, John (Narrative Matters)

(untitled) (The University of New Brunswick, 2011)
In this paper, we share stories of coming to narrative self-study research in graduate studies, and the impact this choice has had on personal and professional directions in ways we could not have imagined when graduate studies were initially embarked upon. Central to self-study narrative inquiry is a focus on life experience as a tool for connection with our own storied pasts. There we find the roots of our present-day perspectives and actions that we can incorporate into our everyday meaning-making, using our emergent understanding to choose present and future possibilities in our relationships.